Kinematics Analysis and Trajectory Planning of UR5 Robot Intersecting Welding Model based on Matlab - Chengchao Yang (Jixie chuandong)
In order to solve the problem of robot welding path planning for welding work at the ball pipe joints，taking the UR5 welding robot as a reference，the models of ball pipe intersection curve is established and the parameter equation of the curve is derived，the D-H coordinate system is established，the forward and reverse directions are solved respectively，by using the Matlab and Adams joint simulation，the trajectory planned path of end effector and the angular velocity and angular acceleration time change curve of each joint are obtained. The test shows that the UR5 welding robot model is correct and reasonable，has good kinematics performance，and has no sudden changes in the posture during the welding process. It also verifies the rationality and reliability of the trajectory planning operation space of the intersecting welding seam. It provides a verification method for welding operations in a complex working environment. The verification method can provide theoretical support for further research on prototype control.